Economic empowerment of rural women and her role in sustainable development (Journal of Planner and Development, 2016)
This study aimed at identifying the level of social empowerment of rural women in the sustainable development in each one of main fields : the ability to change the standard of living and raise the level of the econocomy , discretion in income , the opinion for women work ,the economic independence and self-reliance , the ability to manage their own prajects and decision making productivity , the economice awareness , the competitivens in the labor market , get aloan and the bank facilities . And to identifying the relationship between the percisonality , social , economic variables and the level of economic empowerment of rural women and her role in sustainable development . and to determine the relative contribution of most important varibles in explaining the variance in the level of social empowerment of rural women. The study was conducted in six secters of the rural areas of Baghdad governorat by sleeting one agricultural division representing each seactor them arandum sample from the rural women was selected from these agricultural division the total sample of the study was 270 respondents , the data were collected by personal interview questioning and the statistical program used astatistical package for social science , it analyzes the collected data and the following statistical methods were used : person simple correlation coefficient , stepwise analysis , frequencies and percentages , chi square. The following represent the most important result of the research -focused the majority of respondents were in the high class and the percentage of the field: the ability to change the standard of living and raise the level of the econocom were 70.3% while the field, discretion in income in the high class and the percentage were 53.3% , while the field, the opinion for women work , in the middle class and the percentage 48.8% . the field the economic independence and self reliance economic in the high class and the percentage 43.3% , while the field the ability to manage their own prajects and decision making productivity , in the middle class and the percentage56.3% , the field economice awareness in the middle class and the percentage 45.2% , the filed , the competitivens in the labor market in the middle class and the percentage 47.7% finaly the field, get aloan and the bank facilities in the low class and the percentage51.4% . The result showed that there were amoral positive correlation between the economice empowerment level of the rural women and the following research variables : social status , educational level , dependency , agricultural possessioin, cultural openness attitudes towards modernization ,the special skills and abilities , womens self awareness in the society, the informal social participation. there were four independent variabies explains the variance in the economice empowerment level of rural women in sustainabale development which are : womens self awareness in the society , the informal social participation , cultural openness attitudes towards modernization , the special skills and abilities.